Implementasi Dempster Shafer Dalam Diagnosa Penyakit Impetigo Pada Balita - Nasyuha, Asyahri Hadi; Perangin Angin, Moch Iswan; Marsono, Marsono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The diagnosis of impetigo by using an expert system that uses the source of expertise aims to obtain accurate information in accordance with the symptoms suffered by the patient, this expert system analysis uses the dempster shafer method with mathematical theory for proof based on belief function and plausible reasoning it makes sense to combine separate pieces of information (evidence) to calculate the likelihood of an event that can produce information from experts about the symptoms and solutions of impetigo symptoms accurately and build an expert application system program that is able to diagnose early impetigo in infants and provide solutions and information quickly